(untitled) (International journal of medical sciences, 2026)
This article provides a comprehensive analysis of the pathogenetic mechanisms, clinical manifestations, and diagnostic significance of hemorrhagic syndromes in the pediatric population, with particular emphasis on their association with oncohematological diseases. In childhood, hemorrhagic manifestations are commonly attributed to primary hemostatic disorders such as thrombocytopenia, coagulation factor deficiencies, or vascular wall abnormalities. However, in a considerable number of cases, hemorrhagic syndrome may represent an early clinical sign of underlying malignant hematological conditions. The study explores the molecular and cellular mechanisms linking bone marrow dysfunction to the development of hemorrhagic complications. Special attention is given to impaired hematopoiesis, quantitative and qualitative platelet abnormalities, reduced synthesis of coagulation factors, and endothelial dysfunction as central components of the pathophysiological process. Acute lymphoblastic leukemia, acute myeloid leukemia, aplastic anemia, and myelodysplastic syndromes are discussed as major pediatric oncohematological disorders frequently accompanied by bleeding manifestations.